Transformasi Pendidikan Vokasional di SLB Bina Anggita Yogyakarta: Sebagai Best Practice Kemandirian Kerja - Fitnathul Khikmah; Achadi Budi Santosa; Bambang Sudarsono (CV. Creative Tugu Pena, 2024)
Data from the Ministry of Education and Culture show that the prevalence of autistic children in Indonesia is continuously increasing, with about 1 in 100 children diagnosed with Autism Spectrum Disorder (ASD). According to data from the Ministry of Education and Culture in 2023, approximately 70% of these children face challenges in social and communication aspects, which require specific and targeted educational interventions. This research aims to examine the transformation of vocational education at SLB Bina Anggita Yogyakarta as a best practice in enhancing the work independence of autistic children. The Ministry of Women Empowerment and Child Protection reports 2.4 million cases of autism in Indonesia with a continuously rising prevalence. Data show that children with Autism Spectrum Disorder (ASD) need specialized educational interventions to address their social and communication challenges. Inclusive education programs aim to improve access to and the quality of education, but there is still a need to enhance facilities and resources. This study employs a qualitative approach. Data collection is conducted through in-depth interviews and document analysis, with data validation using a triangulation model, which involves comparing information from different sources and cross-referencing it with data obtained from document reviews. The study's findings indicate that approaches tailored to the individual needs of autistic children are effective in improving their practical skills and job readiness, as well as boosting their confidence. In summary, while significant progress has been made, ongoing efforts are required to develop policies, train teachers, and improve facilities to achieve optimal outcomes in vocational education for autistic children. It is crucial to ensure that autistic children have equal opportunities for success in the workforce and can contribute positively to society.